MODEL OF PROFESSIONAL ORIENTED EDUCATION OF FUTURE ENGINEERS PROBABILITY THEORY AND STOCHASTIC PROCESSES AND ITS IMPLEMENTATION WHEN PRACTICAL LESSONS - Chumak, О.О. (Journal of Information Technologies in Education (ITE), 2015)
The concept model and various approaches to creating of such models are analyzed in the paper. The essence of the model which reflects the process of implementing all the components of designed teaching methodology in their interaction is presented. Professionally oriented education model on the probability theory and stochastic processes course for future engineers is proposed by author. It consists of four parts: theoretical; methodological; content and organization unit; control and effective unit. Applying of methodological foundations of the theory of professionally oriented, heuristic, problem-based learning for forming of intensive learning students’ activities during practical classes is shown. Organizational methods, forms and tools of training, which promote the formation of the internal purposes of students, are presented in the paper. Methods of designing a system of professional-oriented tasks and its applying at the practical classes are given by author. Some ways of developing of students’ skills and abilities during generalization and systematization of knowledge, integrated practical exercises, laboratory works, and business games are considered. Indicators of the formation levels of training activities motivation, professional motivation, self-motivation, levels of knowledge and skills in the probability theory and stochastic processes course, levels of development of professional and analytical thinking, level of applying some e-tools are analyzed by author. The possibility of using measuring tools, including questionnaires, surveys, freshman test, modular tests, exams and special engineering disciplines test, current tests is underlined.